PENGARUH MOTIVASI TERHADAP DISIPLIN KARYAWAN PADA KOPERASI SIMPAN PINJAM AMANAT JAMBI - Sakinah Sakinah; Ubaidillah Ubaidillah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
In this writer took 40 respondents were categorized as age, sex, grade, length of service and level of education. The highest rate of absenteeism in 2010 there were as many as 0.18 %. In the remuneration and incentives in 2014, awarding the highest remuneration in accordance with the plan is 24.46% and the lowest was 11.78% indicates that there are still salary and incentives under the UMP, thus making employee motivation is still very low. Based on the analysis of variable descriptions discipline according to the respondents the average value is quite good and also to some respondents gave excellent ratings. From the results of this analysis is that the linear regression equation simple abtained results Y = 0.168 + 0,94X. This answers the question if the discipline has a positive direction on employee motivation. Coefficient of discipline, 0,94 will increase by 1%, then the motivation will be increased by 0,94%. In statistical tetst disciplinenary effect partially on motivation based calculation, the amount of 8,849 t> t table 1.68385. So there is a significant relationship between the variables of discipline on the motivation of employees at Credit Unions “AMANAT” Jambi region.Keyword: motivation, discipline